Investigation on the effect of cation substitution in Cu2ZnSn(S,Se)4 thin film solar cell - Lie, Stener (Nanyang Technological University, 2020)
Thin film solar cells technology based on Cu2ZnSn(S,Se)4 (CZTSSe) holds great promise due to the abundancy of its constituent elements and their environmentally benign nature. In recent years, developments in achieving higher device performance have been halted due to the inherent Voc deficit of CZTSSe. This poses a huge setback for the successful industrialization of CZTSSe thin film solar cells. Many agreed that cation disordering which emerge due to Cu and Zn similarity in size and chemical environment, is one of the main causes of this issue. Recent progress in cation substitution of CZTSSe with other metals have shown promising result such as Ag with Cu and Cd with Zn. However, incorporation of these elements in CZTSSe is not ideal as they deviate from the earth-abundant and non-toxic motivation of CZTSSe.